La economía circular como desarrollo sostenible, reciclaje y medio ambiente en el gobierno autónomo descentralizado municipal del cantón Tosagua de la provincia de Manabí - Rojas Zambrano, Miguel Alexander (2023)
The main objective of this research was to identify the importance of the circular economy as sustainable development, recycling and the environment, and how it is implemented in the Municipal Decentralized Autonomous Government of the Tosagua canton of the province of Manabí. In addition, different methods, techniques and tools were used, which served as the basis for the subject of study. Likewise, the activities corresponding to the study phases were completed, therefore, in the phase the search for bibliographic information of the first two variables corresponding to the subject was carried out, in the second phase the respective instruments and techniques were used; Among them are the interview with the coordinator of the department of environmental management and recyclers as well as a survey of the citizens of the Tosagua canton, who were the main source of information when identifying the problem and thus providing solutions. Finally, in the third phase, the pilot plan was proposed, providing the necessary activities and strategies that contribute to the development of the research. In this context, it is concluded that it is important that the necessary corrective measures be used by the Municipal Decentralized Autonomous Government of the Tosagua canton, so that the correct use of non-renewable resources is encouraged in society, in addition to having, care, and respect for the environment.